Faunal Diversity and Abundance of Tenebrionidae in Rajasthan - Parihar, D R; Toms, S V (Annals of Arid Zone, 2025)
Tenebrionidae was examined by means of bimonthly surveys carried out using . pitfall traps. A total of 20 species were collected. Distribution and preference of habitats of most of the species were analysed. Sand dune habitat had the highest species dominance, while it was the least in the saline habitat. Relative abundance of some species decreased in the winter season.